Kampanye Gemarikan dalam Upaya Menekan Angka Stunting di Kota Depok - Putri, Nandya Anggita; Paryati, Paryati; MaÃ¡rif, Abdul Aziz (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
This research aims to provide an overview of the public relations campaign process carried out by DKP3 Depok City which is carried out directly or face to face, guided by the Ostergaard campaign model which is relevant to this research. The findings from the research carried out are that the Gemarikan public relations campaign carried out by DKP3 Depok City has gone through four main process stages, namely: identifying problems referring to policies set by the center, increasing fish consumption and looking at data on stunting areas in Depok City, campaign planning stage by checking and adjusting data, determining targets and campaign messages and determining communication channels, campaign implementation stage which is carried out directly and in coordination with other parties, conducting socialization on fish introduction, providing additional food and souvenirs as well as providing psychological support, and evaluation carried out by observing changes in behavior as a measure of campaign success.